2019
DOI: 10.1016/j.clinthera.2019.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Level of Free Hexafluoro-isopropanol in Adults’ Blood and the Incidence of Emergence Agitation After Anesthesia With Different Concentrations of Sevoflurane in Laparoscopic Gastrointestinal Surgery: A Randomized Controlled Clinical Trial

Abstract: Purpose: The aim of the study is to compare the free hexafluoro-isopropanol (HFIP) concentration in adults' blood and the incidence of emergence agitation (EA) after inhaled different concentrations of sevoflurane. Methods: Sixty adult patients planning to undergo laparoscopic gastrointestinal surgery were randomly assigned to 3 groups. Each group received sevoflurane as the volatile anesthetic at different concentrations: 0.5 minimum alveolar concentration (MAC), 1.0 MAC, and 1.5 MAC. The use of sevoflurane w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…It may delay the anesthesia recovery time, even result in the occurrence of emergence agitation during recovery. In this study, longer recovery time and deeper sedation and analgesia were found in the patients with grade B liver dysfunction than the patients with normal liver function during the period of anesthesia recovery (Table 4- 5). Is this phenomenon caused by the retained free HFIP in the body?…”
Section: Discussionmentioning
confidence: 57%
“…It may delay the anesthesia recovery time, even result in the occurrence of emergence agitation during recovery. In this study, longer recovery time and deeper sedation and analgesia were found in the patients with grade B liver dysfunction than the patients with normal liver function during the period of anesthesia recovery (Table 4- 5). Is this phenomenon caused by the retained free HFIP in the body?…”
Section: Discussionmentioning
confidence: 57%
“…Approximately 2% of sevoflurane is metabolised to HFIP by liver cytochrome P450, 26 which can be detected 5 min after sevoflurane application and peaks after 60 min. 26 , 27 Eighty-five percent is rapidly converted into HFIP-glucuronide and eliminated via the kidneys. 26 Concentrations of HFIP in our experiments were similar to previous in vitro 28 and in vivo 24 studies but higher than those measured during sevoflurane anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Airway obstruction, hypoxia, inadequately treated pain, and hemodynamic instability were corrected immediately if they occurred ( Munk et al, 2016 ). A low dose of propofol or midazolam was used for severe agitation, and repeat dosing was instigated until the patient could emerge calmly from general anesthesia ( Demir and Yuzkat, 2018 ; Feng et al, 2019 ). All patients returned to the ward when they were fully awake and met the criteria for PACU discharge.…”
Section: Methodsmentioning
confidence: 99%